Alkaloid gramine to control algal invaders: Algae inhibition and gramine persistence. (September 2019) - Canton, Michael C.; Holguin, F. Omar; Boeing, Wiebke J.
Abstract: Algae cultivation has many applications, however, limiting system contamination is imperative. Algae competitors invading cultivation systems can negatively interfere. Here, we test the potential usefulness of an indole alkaloid allelochemical (gramine) to control invasions of Chlorella sorokiniana cultures by undesired Coelastrella sp. Chlorella sorokiniana and Coelastrella sp. cultures were exposed to 0, 4, 16, 32, and 64 mg gramine L −1 (n = 4) in test tubes in a rotator drum. Algae growth was measured by optical density at 750 nm and gramine concentration via high performance liquid chromatography (HPLC) over 16 days. C. sorokiniana growth was significantly inhibited at gramine concentrations above 16 mg L −1, while Coelastrella sp. responded to concentrations as low as 4 mg L −1 . This shows that 4 mg L −1 gramine might aid Chlorella cultures when invaded by a competitor such as Coelastrella . HPLC results indicate that algae remove gramine from water, allowing algae cultures to recover. Highlights: Alkaloid allelochemical gramine can be used as an allelopathy model for algae. Gramine can also be used to control invasions of undesired algal competitors. Invader Coelastrella is more sensitively to gramine than target species Chlorella. Live algae remove gramine from water over time.